Research progress of spontaneous ruptured hepatocellular carcinoma: Systematic review and meta-analysis - Wang, Chunling; Huang, Xiaozhun; Lan, Xiaofeng; Lan, Dongmei; Huang, Zhangkan; Ye, Shu; Ran, Yihong; Bi, Xinyu; Zhou, Jianguo; Che, Xu (Frontiers in Oncology, 2022)
Background Spontaneously ruptured hepatocellular carcinoma (rHCC) with hemorrhage is characterized by rapid onset and progression. The aim of this systematic review was to explore the current studies on rHCC with hemorrhage and determine the optimum treatment strategy. Method The PubMed, Web of Science, Embase, and the Cochrane Library databases were searched for studies reporting survival outcomes with comparison between emergency resection (ER) and transarterial embolization following staged hepatectomy (SH) were included by inclusion and exclusion criteria, the perioperative and survival data were statistically summarized using Review Manager 5.3 software. Result A total of 8 retrospective studies were included, with a total sample size of 556, including 285 (51.3%) in the ER group and 271 (48.7%) in the SH group. The perioperative blood loss and blood transfusion volume in the SH group were less than those in the ER group, and there were no significant differences in the operative time, incidence of complications, mortality and recurrence rate of tumors between the two groups. The 1-, 2-, 3-year overall survival and 1-, 2-, 3-, 5-year disease-free survival of the ER group were not significantly different from those of the SH group, and the 5-year overall survival rate of ER group was lower than that of the SH group (hazard ratios=1.52; 95% confidence intervals: 1.14-2.03, P=0.005). Conclusion There was no significant difference in the short-term efficacy of ER or SH in the treatment of ruptured HCC, and SH was superior to ER in the long-term survival.